ANALYSIS OF GAS RATIO DRILLING TO IDENTIFY THE G-80 SANDSTONE RESERVOIR FOR WELL CORRELATION IN THE SEMBERAH FIELD, KUTAI BASIN - Battu, Desianto Payung; Adi Tonggiroh; Meutia Farida (GEOMATE Journal, 2025)
Data uncertainty caused by drilling activities can affect the accuracy of distinguishing productive from non-productive zones, especially in fluid characterization and reservoir evaluation, which are core objectives of geoscience. Each well in Semberah has an objective to penetrate several layers of target, including both oil and gas reservoirs. Gas ratio analysis is an established method for identifying reservoir characteristics by analyzing formation fluid molecules that rise to the surface with the drilling mud when the drill bit breaks through the formation. The integration of drilling data, well logs, and gas analysis from six wells in Semberah has led to a deeper understanding of reservoir potential during drilling. The analysis focused on G-80 sandstone, one of the reservoirs found throughout the Semberah field. Similar trends were observed in total gas compared to resistivity log values, which ranged from 42 to 700 units, versus resistivity measurements from 6.0 to 18.7 ohms. The C1/Sum C ratio ranged from 0.8 to 0.9, WH value indicated dry gas, BH value more 50 is gas while below 50 is water or undeveloped reservoir. The fluid mobility characteristic of the estimated potential porosity gas ratio indicates an approach to porosity values derived from petrophysical analysis. The results of this study demonstrate that gas ratio analysis can support geoscience research and contribute to a broader understanding of the area.